Analisis Blending Kualitas Batubara Pit Pe Seam A, B dan C Untuk Memenuhi Nilai Kadar Sulfur Pltu Keban Agung Pt Priamanaya Energi Lahat Sumatera Selatan - Andini, Ubai Dila; Yovanda, Ridho; Permatasari, Syelly Eka (Jurnal Inovasi Global, 2025)
The Keban Agung Power Plant is a Steam Power Plant located in Kebur Village, West Merapi District, Lahat Regency, which requires coal as its main fuel with quality that meets the standards of PLTU specifications to optimize the combustion process and reduce SO2 emissions. One of the most important coal quality parameters that need to be considered in coal suppliers to coal-fired power plants is sulfur content. Priamanaya Energi Coal Pit Coal seam A has a sulfur content of 0.16, seam B of 0.28, while seam C of 0.91 and 1.12. High sulfur levels cannot enter the coal-fired power plant because it can cause damage to the equipment such as rusting (corrosion). Therefore, this study aims to analyze the quality of seam coal A, B, and C used in coal blending activities to meet the sulfur content value of seam C coal in accordance with the specification standards of the Keban Agung PLTU which is at 0.1 to 0.5. Based on the 10 calculations of the coal quality blending test, it shows that blending with a composition of 8:1 with a tonnage of 2430 tons succeeded in reducing the sulfur content value of coal seam C to 0.31.